PENENTUAN KESELARASAN STRATEGI TEKNOLOGI INFORMASI DAN STRATEGI TEKNOLOGI INFORMASI DAN STRATEGI BISNIS PADA SALAH SATU BANK SYARIAH WILAYAH JAKARTA MENGGUNAKAN METODE LUFTMAN - Triningsih Triningsih; Indah Puspitorini; Herudini Subariyanti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Information Technology (IT) is growing very rapidly. Information Technology is a technology that can be used to get more benefits from an ongoing system The application of information technology systems will be useful if the application is in accordance with the goals, vision and mission of the organization that has been translated into business strategies and information technology strategies. The alignment between the information technology strategy and business strategy will provide added value in the form of competitive advantage in business competition. The application of good information technology has a big influence in achieving the goals of an educational institution, it is hoped that this can be implemented properly. This can be seen from the application of the information technology whether it has conformed to the process carried out within the educational institution. Luftman has built a method that can help a company know the level of strategic maturity that the company has. Luftman's method is known as the Luftman Framework or the Luftman strategic alignment maturity model. An organization if the information technology maturity has approached expectations that are expected, the organization of the technology will be more effective in carrying out the process of aligning information technology and business, so that the alignment process can take place better